1986
DOI: 10.1002/1097-0142(19861115)58:10<2355::aid-cncr2820581033>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Unmet psychological, social, and economic needs of persons with cancer in pennsylvania

Abstract: Six hundred twenty-nine persons with cancer (PWC) selected from the Pennsylvania Cancer Registry plus 397 nonprofessional (support) persons involved in their care (SP) were interviewed to determine their views of the unmet psychological, social and economic needs of PWC. The most frequently mentioned unmet need was for help in dealing with emotional problems (estimated at 25% of PWC state-wide). Other unmet need estimates ranged from 14% for financial to 4% for transportation, with 59% of PWC reporting at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
84
1
4

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(99 citation statements)
references
References 9 publications
10
84
1
4
Order By: Relevance
“…These findings are in accordance with results from previous studies (Stam et al, 1986;Houts et al, 1986;Sullivan et al, 1986). Therefore, psychosocial intervention should focus on these principal areas of need for cancer patients in order to be maximally effective.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These findings are in accordance with results from previous studies (Stam et al, 1986;Houts et al, 1986;Sullivan et al, 1986). Therefore, psychosocial intervention should focus on these principal areas of need for cancer patients in order to be maximally effective.…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have identified many categories of psychosocial need for cancer patients using different methods of assessment (Watson, 1983;Heinrich et al, 1984;Houts et al, 1986;Stam et al, 1986;Sullivan et al, 1986). Some provide valuable qualitative information on the needs of patients through interviews using open-ended questions, while others provide quantitative results by means of forced-choice response questions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Such results are uniform with other research, which show high levels of unmet needs in the psychological 7,12,14 physical/daily living [15][16][17] and communication/information domains. 14 The survey by Sanson-Fisher et al 1 also demonstrated that subgroups of patients encountered different types of needs.…”
Section: General Needs Of Cancer Patientssupporting
confidence: 84%
“…Such research is important for a number of reasons: It allows for a more detailed understanding of how young people who have a parent with cancer perceive, experience and express their needs [11], and it provides direct assessment of the type, number and magnitude of these needs and whether they have been met. An important application of such knowledge is in the planning of better psychosocial intervention programs for this group [11,16], particularly as clinicians and service providers move from service-led toward need-led practice [17]. Finally, a need-based research can also lead to an understanding of the factors that contribute to resilience in these young people, which may help to prevent or reduce the likelihood of developing long-term mental health problems.…”
Section: Introductionmentioning
confidence: 99%